A phenomenological approach to stress corrosion cracking - Nehrozoğlu, Mehmet Aydemir. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
The applicability of the J-integral to SSC in the elasticplastic range is investigated by using precracked cantilever beam specimens of low carbon steel in 6N H2S04 solution. The correlation of J-integral with the incubation time suggests the existence of a threshold value of J.
Keywords: Stress corrosion.